Exploring the Anionic Surfactant Concentrations and Biological Contamination in Yamuna River: Identifying Potential Sources and Mitigation Strategies - Arora, Jayati; Chauhan, Abhishek; Ranjan, Anuj; Singh, Reetu; Ismail, Khatib Sayeed; Dimri, Amita G.; Biswas, Rima; Jindal, Tanu (Asian Journal of Chemistry, 2023)
Anionic surfactants in the river, particularly downstream in Delhi, have created massive foam-like conditions which may be harmful to aquatic life and humans that come in contact. The present study focussed on the quantification of anionic surfactants, biological contaminants in terms of total bacterial count, total and faecal coliform bacteria and qualitative analysis of pathogenic bacteria from the samples acquired from different sites of Yamuna river. The concentration of anionic surfactants was observed to be between 0.42-3.89 mg L-1 at Okhla barrage, which was significantly high as compared to Wazirabad barrage and ITO bridge. The total bacterial count of Okhla barrage was observed more as compared to Wazirabad barrage and ITO Bridge ranging between 9.7 × 106 to 9.1 × 108 CFU/mL. The findings of total coliform bacteria were observed to be consistently high at Wazirabad barrage ranging between 1.3 × 103 to 9.0 × 104 MPN/100 mL. Qualitative analysis of pathogenic bacteria showed the presence of P. aeruginosa, Salmonella sp., E. coli and S. aureus. Based on the results obtained in the study, it was inferred that the water quality of Yamuna river at Wazirabad barrage, ITO Bridge and Okhla barrage was poor and thus requires regular monitoring and call for immediate effective mitigation strategies.